UTILIZATION OF DIGITAL QUR'AN APPLICATIONS IN ISLAMIC RELIGIOUS EDUCATION LEARNING - Syaiful Rahman; Muhammad Kholil (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
The development of information and communication technology in the digital era has brought significant transformations in the field of education, including in Islamic Religious Education (PAI) learning. This study aims to describe the use of digital Qur’an applications as an innovation in Islamic Religious Education (PAI) learning and identify its impact on students' motivation and understanding of the Qur’an. This study uses a descriptive qualitative approach, with data collected through observation, interviews, and documentation involving teachers and students at a secondary school in Situbondo. The findings indicate that the use of digital Qur’an applications, such as Qur'an Kemenag and Muslim Pro, facilitates students in reading, listening, and understanding the meaning of Qur’anic verses interactively. Teachers also utilize digital interpretation and audio recitation features to enhance contextual and engaging learning experiences. However, challenges such as limited digital literacy and inadequate access to technological devices still hinder optimal implementation. This study concludes that the integration of digital Qur’an applications into PAI learning effectively supports the achievement of Islamic education goals, especially in strengthening students' spirituality, Qur’anic literacy, and moral character. It is recommended that digital literacy training be provided to Islamic Education teachers so that technology-based learning management can be more effective and sustainable.